A comprehensive review on femtosecond laser polishing of silicon nitride: fundamentals, current progress, and industrial outlook - Jian, Huang; Pimsarn, Monsak; Chuwattanakul, Varesa; Eiamsa-ard, Smith (My University, 2026)
Silicon nitride ((Formula presented.)) ceramics are indispensable in aerospace bearings and semiconductor substrates due to their exceptional mechanical and thermal properties. However, achieving damage-free, atomic-level surface finishes remains problematic. Traditional mechanical polishing induces subsurface microcracks, while chemical mechanical polishing (CMP) is plagued by low material removal rates and environmental toxicity. This review critically evaluates femtosecond laser polishing as a transformative, “green” non-contact alternative. We first elucidate the laser-matter interaction mechanisms specific to wide-bandgap (Formula presented.) ((Formula presented.) eV), clarifying how multiphoton absorption enables “cold ablation” by suppressing the heat-affected zone (HAZ) via the two-temperature model (TTM) dynamics. A distinct material removal mechanism driven by rapid thermal decomposition ((Formula presented.)) and phase explosion is highlighted. Synthesizing recent experimental data, we establish a quantitative process window. Operating slightly above the ablation threshold ((Formula presented.)) with high spot overlap (70%–90%) is critical to balance surface leveling against the incubation effect, which otherwise triggers porosity. Furthermore, we address the unique challenges of inducing periodic structures (LIPSS) on dielectric surfaces and propose a hybrid manufacturing strategy—integrating high-speed laser roughing with CMP finishing—to resolve efficiency constraints. Finally, an industrial roadmap involving high-throughput polygon scanners and AI-driven closed-loop control is outlined, providing a comprehensive reference for advancing femtosecond laser polishing toward scalable, high-precision manufacturing.
Keywords: cold ablation mechanism; femtosecond laser polishing; green manufacturing; hybrid polishing strategy; incubation effect; silicon nitride (Si3N4)